2006
DOI: 10.1111/j.1365-313x.2006.02909.x
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of the human transferrin receptor in plant cells: effects of tyrphostin A23 and brefeldin  A

Abstract: SummaryPlant cells possess much of the molecular machinery necessary for receptor-mediated endocytosis (RME), but this process still awaits detailed characterization. In order to identify a reliable and well-characterized marker to investigate RME in plant cells, we have expressed the human transferrin receptor (hTfR) in Arabidopsis protoplasts. We have found that hTfR is mainly found in endosomal (Ara7-and FM4-64-positive) compartments, but also at the plasma membrane, where it mediates binding and internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 92 publications
4
95
0
Order By: Relevance
“…TyrA23 can specifically prevent the interaction between cargo motifs destined for endocytosis and the m2 subunit of the clathrin binding AP-2 adaptor complex (Banbury et al, 2003). A recent report showed that TyrA23 efficiently inhibited interaction between the human transferrin receptor and a m-adaptin subunit and then blocked the internalization of the human transferrin receptor in Arabidopsis protoplasts (Ortiz-Zapater et al, 2006). Thus, it is widely used to inhibit clathrin-dependent endocytosis without causing discernible morphological changes (Dhonukshe et al, 2007;Robinson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…TyrA23 can specifically prevent the interaction between cargo motifs destined for endocytosis and the m2 subunit of the clathrin binding AP-2 adaptor complex (Banbury et al, 2003). A recent report showed that TyrA23 efficiently inhibited interaction between the human transferrin receptor and a m-adaptin subunit and then blocked the internalization of the human transferrin receptor in Arabidopsis protoplasts (Ortiz-Zapater et al, 2006). Thus, it is widely used to inhibit clathrin-dependent endocytosis without causing discernible morphological changes (Dhonukshe et al, 2007;Robinson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that tyrphostin A23 alone does not inhibit FM4-64 uptake of untreated cells (this study; Ortiz-Zapater et al, 2006;Dhonukshe et al, 2007), indicates that constitutive endocytotic traffic can continue in the presence of this inhibitor. This suggests that, although constitutive and cryptogein-induced endocytosis appears to be mediated by morphologically identical CCPs at the plasma membrane, the regulatory mechanisms involved could be different.…”
Section: Pharmacological Interference Supports a Role For Rme In Crypmentioning
confidence: 99%
“…Some tyrphostin members such as tyrphostin A23 have also been used to inhibit endocytosis: specific inhibition of clathrin-mediated endocytosis due to the interaction between tyrphostin A23 and the subunit m2 of the AP-2 complex, one component of the membrane coat associated with clathrin, has been reported (Banbury et al, 2003). This inhibitor has been used at concentrations of 500 or 350 mM in mammalian cells to inhibit internalization of the Tf-R (Banbury et al, 2003) or the prion protein (Taylor et al, 2005), and in plant protoplasts to inhibit human Tf-R internalization (Ortiz-Zapater et al, 2006). More recently, tyrphostin A23 was utilized at a concentration of 30 mM to inhibit internalization of the PIN auxin efflux carrier and different plasma membrane proteins in Arabidopsis roots (Dhonukshe et al, 2007).…”
Section: Cryptogein-stimulated Endocytosis Is Blocked By Tyrphostin A23mentioning
confidence: 99%
See 2 more Smart Citations